Chromatic Pupillometry in Isolated Rapid Eye Movement Sleep Behavior Disorder. Issue 1 (7th October 2021) - La Morgia, Chiara; Romagnoli, Martina; Pizza, Fabio; Biscarini, Francesco; Filardi, Marco; Donadio, Vincenzo; Carbonelli, Michele; Amore, Giulia; Park, Jason C.; Tinazzi, Michele; Carelli, Valerio; Liguori, Rocco; et al.
Abstract: Background: Melanopsin retinal ganglion cell (mRGC)‐mediated pupillary light reflex (PLR) abnormalities have been documented in several neurodegenerative disorders including Parkinson's disease. Overall, isolated rapid eye movement (REM) sleep behavior disorder (iRBD) represents the strongest prodromal risk factor for impending α‐synucleinopathies. Objectives: To quantitatively compare PLR and mRGC‐mediated contribution to PLR in 16 iRBD patients and 16 healthy controls. Methods: iRBD and controls underwent extensive neuro‐ophthalmological evaluation and chromatic pupillometry. In iRBD, PLR metrics were correlated with clinical variables and with additional biomarkers including REM atonia index (RAI), DaTscan, and presence of phosphorylated‐α‐synuclein (p‐α‐syn) deposition in skin biopsy. Results: We documented higher baseline pupil diameter and decreased rod‐transient PLR amplitude in iRBD patients compared to controls. PLR rod‐contribution correlated with RAI. Moreover, only iRBD patients with evidence of p‐α‐syn deposition at skin biopsy showed reduced PLR amplitude compared to controls. Conclusion: The observed PLR abnormalities in iRBD might be considered as potential biomarkers for the risk stratification of phenoconversion of the disease. © 2021 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society